Mitochondrial function following downhill and/or uphill exercise training in rats. Issue 5 (31st August 2016) - Schlagowski, Anna‐Isabel; Isner‐Horobeti, Marie‐Eve; Dufour, Stéphane P.; Rasseneur, Laurence; Enache, Irina; Lonsdorfer‐Wolf, Evelyne; Doutreleau, Stéphane; Charloux, Anne; Goupilleau, Fabienne; Bentz, Isabelle; Charles, Anne Laure; Kouassi, Blah Y.; et al.
ABSTRACT: Introduction : The goal of this study was to compare the effects of downhill (DH), uphill (UH), and UH‐DH exercise training, at the same metabolic rate, on exercise capacity and skeletal muscle mitochondrial function. Methods : Thirty‐two Wistar rats were separated into a control and 3 trained groups. The trained groups exercised for 4 weeks, 5 times per week at the same metabolic rate, either in UH, DH, or combined UH‐DH. Twenty‐four hours after the last training session, the soleus, gastrocnemius, and vastus intermedius muscles were removed for assessment of mitochondrial respiration. Results : Exercise training, at the same metabolic rate, improved maximal running speed without specificity for exercise modalities. Maximal fiber respiration was enhanced in soleus and vastus intermedius in the UH group only. Conclusions : Exercise training, performed at the same metabolic rate, improved exercise capacity, but only UH‐trained rats enhanced mitochondrial function in both soleus and vastus intermedius skeletal muscle. Muscle Nerve 54 : 925–935, 2016